Real and illusory perceptions of patients in induced coma - Simone Costa Silva; Laura Menezes Silveira; Leila Maria Marchi-Alves; Isabel Amélia Costa Mendes; Simone de Godoy
ABSTRACT Objective: To identify, in the scientific literature, real and illusory perceptions of adult patients in induced coma. Methods: This is an integrative review of 15 primary studies from the Medline, Web of Science, LILACS, CINAHL and SCOPUS databases. Results: The main memories reported after induced coma were thirst, cold, and pain. In some studies, patients reported they were unable to tell whether they were awake or dreaming, whether it was real or unreal. Satisfactory memories were reported by patients related to the care received and the use of bedside journals. Conclusion: Evidence showed a number of studies aiming to identify delirium, but without a focus on analyzing real or illusory perceptions of patients after induced coma. Thus, this integrative review identified scientific evidence of memories related to perceptions of sedated patients in the intensive care unit.